Solving the Limits of Algebraic Functions using the Guided Inquiry Learning Approach - Rahma, Nadya Alvi; Nurhalimah, Wahyu (Transcendent Journal of Mathematics and Applications, 2022)
This article is a quantitative study that seeks to ascertain the impact of the guided inquiry learning model on students' mathematical creative thinking skills in the context of limiting algebraic functions. The study was conducted at MAN 3 Blitar with research subjects from two level IX classes. Data derived from observations, documentation, and post-test questions. SPSS 24.0 was used to calculate the data, which was then compared to determine the correlation between the two samples. Based on expert validation results, the interactive multimedia developed is feasible with an average sigma percentage of 5%. Following research and observation, it is possible to conclude that the guided inquiry learning model has an effect on students' mathematical creative thinking skills. The guided inquiry learning model has a 62% influence on students' mathematical creative thinking skills.